Kripto Aset dalam Keuangan Syariah: Tinjauan Sistematis tentang Tantangan dan Peluang Kesesuaian Syariah - Ikmaliyah, Mirzah; Roza, Elvira Mey; Amanda, Asty; Rahayu, Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This article presents a systematic literature review (SLR) on the challenges and opportunities of Shariah compliance in the use of crypto assets within the Islamic financial system. Drawing on 52 peer-reviewed articles published between 2020 and 2025, this study employed bibliometric analysis using VOSviewer to map key themes, terminologies, and scholarly trends. The review focuses on three core dimensions: (1) fiqh muamalah perspectives, (2) regulatory and legal frameworks, and (3) emerging business models in Shariah-compliant crypto finance. The results reveal that dominant keywords such as “cryptocurrency,” “Islamic finance,” and “Shariah compliance” indicate growing scholarly attention to ethical and jurisprudential dimensions beyond technological innovation. Five major thematic clusters were identified, including Islamic ethical foundations, digital regulation, halal financial instruments, global fatwa comparisons, and implementation barriers. The review also highlights a fragmented understanding of crypto legitimacy across fatwa institutions and a lack of empirical studies addressing Shariah-compliant adoption frameworks. Therefore, multi-stakeholder collaboration between regulators, scholars, and fintech practitioners is crucial to develop a comprehensive Shariah-based evaluative framework. These findings aim to guide future policies and contribute to building a trustworthy, inclusive halal crypto ecosystem aligned with the objectives of Islamic law (maqashid al-shariah).